Pengaruh Morfologi Serbuk Silika Nanopartikel Terhadap Efektivitas Poles Pewarnaan Gigi - Siagian, Rivita; Evelyna, Angela; Purwasasmita, Bambang Sunendar (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2014)
Silica is a product which is produced from hydrated silica available in a variety of particle sizes and characteristics. Silica is easy to find and mechanically used as stain remover. Large size of silica particles can cause deep scratches on the teeth and restaining can occurred so that nanoscale be used. The aim of this research to determine the result test from synthesis silica nanoscale with morphology nanosphere and nanorod and differences effectiveness of abrasion with different morphology. This research was an experimental study with 27 sample divided into three groups. The first group were polished with silica nanosphere, the second group with silica nanorod and the third group with a mixture of both silica. Tooth samples was captured then flowed by a solution of coffee during 2 months until the color changes and last taken picture of it. The tooth staining was polished with three body wear process with three abrasive particles from three groups was applied use to rubber cup and low speed handpiece then analyzed using software image J. The data were statistically analyzed using ANAVA test with p<0,05 and continued with unpaired t-test. Research conclude that the result test of synthesis nanoparticle silica obtained morphology nanosphere and nanorod and there are also differences effectiveness abrasion of silica with different morphology.